Widespread School. New learning landscapes in the Reggio Emilia Educational Experience - Conte , Valentina; Manera, Lorenzo (Revista Eletrônica de Educação, 2024)
Learning spaces emerge as crucial elements in shaping the educational experience in a rapidly changing academic environment. This article examines the impact of physical and digital environments on learning, highlighting how the configuration of spaces can significantly influence student performance and engagement. Analyzing different methodologies and space configurations highlights best practices for promoting effective and inclusive learning. In particular, the “Widespread School” is discussed as an example of adapting educational spaces to contemporary needs for flexibility, interaction, and health security. The article concludes with recommendations for designing spaces that facilitate various modes of learning and interaction and their potential for adaptation to future pedagogical innovations